Olive Oil Polyphenols Differentially Inhibit Smooth Muscle Cell Proliferation through a G1/S Cell Cycle Block Regulated by ERK1/2 - Abe, Rei; Beckett, Joel; Abe, Ryuzo; Nixon, Alexander; Rochier, Adrienne; Yamashita, Norio; Sumpio, Bauer (International Journal of Angiology, 2012)
We hypothesized that polyphenols contained in olive oil play a role in reducing the risk of atherosclerosis. The aim of this study was to determine if the polyphenols in olive oil, oleuropein (Ole), hydroxytyrosol (HT), and tyrosol (Tyr) could inhibit smooth muscle cell (SMC) proliferation through its influence on cell cycle regulation. Bovine vascular SMC were cultured in the presence of Ole, HT, or Tyr at concentration of 1, 10, or 100 μmol/L. On days 1, 3, and 5, numbers of cells were counted. Cell cycle analysis was performed by flow cytometry on day 1 after SMC were stained with propidium iodide. Cell populations grown in the presence of Ole or HT at 100 μmol/L concentration were significantly inhibited after 5 days of exposure. Tyr had a similar tendency but it did not attain significance. Cell cycle analysis revealed that 66% of cells were in G1 phase in Ole group, compared with 48% in control group. To examine the cell cycle block between G1 and S phases, we performed Western blotting and found that ERK1/2 activation was inhibited by Ole or HT. We conclude that olive oil polyphenols could inhibit SMC proliferation through a cell cycle block between G1 and S phases which may be regulated by ERK1/2. These results demonstrate a mechanism by which olive oil consumption may be atheroprotective by inhibiting SMC proliferation.
Keywords: olive oil; oleuropein; hydroxytyrosol; tyrosol; smooth muscle cell proliferation; ERK1/2